Whitman and Nietzsche A Comparative Study of Their Thought - Stavrou, C.N (UNC Studies in the Germanic Languages and Literatures, 1964)
This volume will be a great aid to students and scholars alike in American literature, American thought, the history of ideas, and comparative literature. Stavrou draws from the entire bodies of work by Whitman and Nietzsche to explore the parallels in the authors' conceptions of paradox, the totality of life, and solitude among other themes in this exploration of the underlying philosophical similarities of these two great writers of the nineteenth century.